(untitled) (Iranian Journal of Kidney Diseases, 2021)
Introduction. Previous studies have suggested that linagliptin may represent renoprotective effects besides its anti-hyperglycemic properties in patients with type 2 diabetes. However, there is a lack of decisive evidence to support this assumption. This study aimed to address the effect of linagliptin in type 2 diabetic patients with severely increased albuminuria. Methods. In this randomized double-blind, placebo-controlled clinical trial, type 2 diabetic patients with severely increased albuminuria (albuminuria ≥ 300 mg/24 h) were enrolled. Patients were randomized to linagliptin (5 mg/d) and placebo based on a computer-generated list of random numbers. Biochemical (fasting blood sugar (FBS) (mg/dL), hemoglobin A1c (HbA1c) (%), proteinuria (mg/24h), blood urea nitrogen (BUN) (mg/dL), serum creatinine (mg/dL)) and clinical variables (weight (kg), systolic, and diastolic blood pressure (mmHg)) were measured at baseline and 3 and 6 months post intervention. Results. At baseline, no statistically significant difference was detected in demographic characteristics between the two groups (P > .05). A significant decrease was observed in proteinuria, FBS, weight, SBP, and DBP in the intervention group after 6 months (Ptime < .05), however; none of the clinical and biochemical variables showed a significant difference between groups after 6 months (Pgroup > .05). Conclusion. Linagliptin may serve as a renoprotective therapeutic option in diabetic patients with severely increased albuminuria due to its role in proteinuria reduction. Results of this study can be used for future large-scale, long-term studies investigating the renoprotective effects of linagliptin in patients with diabetic nephropathy. DOI: 10.52547/ijkd.6110